Produção de mudas a partir de rizomas de bambusa vulgaris sob irrigação com água salina - Castelo Branco, Lourenço Marreiros (2016)
The bamboo culture has the characteristic of having native species on every continent except Europe. Brazil has more than 240 different plant species and is the champion in biodiversity of the Americas. The ravaging salinity, worldwide, around 930 million ha and a major cause of the influence of salts is inadequate management of irrigation water in arid and semi-arid regions. Thus, there is a need to have more information about the growth of the bamboo culture and its tolerance to salinity under the conditions of de Baturité region, Ceará. The study was conducted at the Experimental Farm Piroás, belonging to the University of International Integration Lusophone African-Brazilian (UNILAB), municipality of Redemption, Ceará, in the period from July to December 2015. The experiment was a completely randomized design (CRD) with five treatments and six repetitions. The treatments consisted of five levels of salinity of irrigation water: 0.5 (control); 1.5; 2.5; 3.5 and 4.5 dS.m-1, S1 to S5, respectively; totaling 30 plants. Bamboo seedlings were planted through rhizomes, polyethylene vessels with 60 liter capacity, with spacing of 1.0 m between rows and 0.80 m between vessels on the same line. Irrigation management was based on the evaporation of the "A" class tank, and the water depth applied with a two-day irrigation interval and in order to restore 100% of the reference evapotranspiration (ETo). The total depth applied during the 120-day growing season was 555.2 mm. They were evaluated every 7 days biometric variables (plant height, stem diameter and number of leaves). Absolute growth rates were calculated (TCA) and growth rates (RGR). Soil samples were collected to measure the electrical conductivity of soil extract: water (EC 1: 1). Gas exchange (photosynthesis, stomatal conductance, transpiration) and the relative chlorophyll index were measured at 80 and 120 DAT. At the end of the experiment was measured the production of dry biomass of shoot and were determined to Na+ ions, K+, Cl- and Na / K ratio in the stems and leaves. The electrical conductivity of the saturated soil extract (CEes) gave a linear increase according to the increase in the levels of salts in the irrigation water. The increase in salinity of irrigation water reduced the height, stem diameter, number of leaves and biomass production of bamboo plants, with the most significant reductions in salinities above 2.5 dS m-1. The net photosynthetic rate (A), stomatal conductance (gs), transpiration (E) and the relative chlorophyll index (CRI) showed a linear decrease as increase in water salinity and exposure to salts. The concentrations of Na+ and K+ were inversely proportional, both in the stem and leaves, indicating the existence of ionic competition in the absorption process. The lower levels of Na+ and lowest ratios Na/K in the leaves indicate that bamboo plants present the ion retention mechanism stems, reducing the impact on photosynthetic tissues. For most of the variables used it verifies that the bamboo showed tolerance or moderately tolerant of water with salinity up to 2.5 dS m-1, being an indication that such waters can be used in the initial stage of culture growth. The plant height was not an efficient variable to detect the degree of tolerance to salinity of bamboo, possibly by the intensification of salt stress affects more tiller production than the height of the main branch.